2003
DOI: 10.1590/s1517-83822003000200006
|View full text |Cite
|
Sign up to set email alerts
|

New bioemulsifiers produced by Candida lipolytica using D-glucose and babassu oil as carbon sources

Abstract: Candida lipolytica IA 1055 produced extracellular biosurfactants with emulsification activity by fermentation using babassu oil and D-glucose as carbon sources. Natural seawater diluted at 50% supplemented with urea, ammonium sulfate, and phosphate was used as economic basal medium. The best results were achieved with the YSW-B2 medium, which contained urea, ammonium sulfate, and babassu oil and with YSW-B3 medium, which contained urea, ammonium sulfate, phosphate, and babassu oil, kept under fed batch ferment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 12 publications
1
16
0
5
Order By: Relevance
“…Different nitrogen compounds have been used for the production of biosurfactants, such as urea, 43 peptone, 44 yeast extract, 11,[45][46][47] ammonium sulphate, 20 ammonium nitrate, 37 sodium nitrate, 34 meat extract and malt extract, 48 etc. Yeast extract is the most used nitrogen source for biosurfactant production, but its concentration depends on the microorganism and the culture medium.…”
Section: Nitrogen Sourcementioning
confidence: 99%
“…Different nitrogen compounds have been used for the production of biosurfactants, such as urea, 43 peptone, 44 yeast extract, 11,[45][46][47] ammonium sulphate, 20 ammonium nitrate, 37 sodium nitrate, 34 meat extract and malt extract, 48 etc. Yeast extract is the most used nitrogen source for biosurfactant production, but its concentration depends on the microorganism and the culture medium.…”
Section: Nitrogen Sourcementioning
confidence: 99%
“…The types of biosurfactants include lipopeptides synthesized by many bacilli and other species, glycolipids synthesized by Pseudomonas and Candida species, phospholipids synthesized by Thiobacillus thiooxidans, and polysaccharide-lipid complexes synthesized by Acinetobacter species, or even the microbial cell surface itself [31,34].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the surface tension reductions achieved by Y. lipolytica may be considered promising under the conditions of runs 2, 4, 7 and 15 of this work. The importance of monobasic phosphate potassium in bioemulsifier production in sea water is corroborated by studies that reported the production of emulsifiers by C. lipolytica in sea water diluted to 50%, supplemented with sources of nitrogen and phosphorus, using corn oil (Albuquerque et al, 2006) and babassu oil (Harrop-Vance et al, 2003) as carbon sources. Mariano et al (2008) evaluated the production of a biosurfactant by Staphylococcus hominis, Kocuria palustris and Pseudonomas aeruginosa LBI using a mineral medium in the presence of diesel oil (weathered and commercial) at 1, 5, 10, 20 and 30% v/v as a low cost substrate.…”
Section: Culture Medium Investigation For Bioemulsifier/ Biosurfactanmentioning
confidence: 80%